2016
DOI: 10.1111/1750-3841.13418
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Cellular Antioxidant Activities of Chicken Breast Muscle Subjected to Various Thermal Treatments Followed by Simulated Gastrointestinal Digestion

Abstract: The effect of thermal treatments on chemical and cellular antioxidant activities of chicken breasts subjected to in vitro gastrointestinal digestion was investigated. Breast of Korat crossbred chicken (KC) and commercial broiler (BR) were cooked under various conditions, namely heating at 70 °C for 30 min (H-0.5) and 24 h (H-24), autoclaving (AC) at 121°C for 15 min (AC-15) and 60 min (AC-60). Protein digestibility decreased upon the extreme thermal treatment of AC-60. The H-0.5 improved metal chelating activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…SPPH by GID from autoclaving pretreated sample presented the highest ÁOH scavenging activity and Fe 2+ -chelating capacity which were 35.13% and 66.07% for GID2 respectively (P < 0.05). It was reported that hydrolysates produced by GID from chicken breast muscle subjected to autoclaving pretreatment exhibited good cellular antioxidant activities (Sangsawad et al, 2016). The combination of autoclaving pretreatment and enzymatic hydrolysis was able to improve the antioxidant activities of soy protein isolate due to the unfolding of proteins and the cleavage of disulphide bonds (Yoo & Chang, 2016).…”
Section: Effect Of Pretreatment On Antioxidant Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…SPPH by GID from autoclaving pretreated sample presented the highest ÁOH scavenging activity and Fe 2+ -chelating capacity which were 35.13% and 66.07% for GID2 respectively (P < 0.05). It was reported that hydrolysates produced by GID from chicken breast muscle subjected to autoclaving pretreatment exhibited good cellular antioxidant activities (Sangsawad et al, 2016). The combination of autoclaving pretreatment and enzymatic hydrolysis was able to improve the antioxidant activities of soy protein isolate due to the unfolding of proteins and the cleavage of disulphide bonds (Yoo & Chang, 2016).…”
Section: Effect Of Pretreatment On Antioxidant Activitiesmentioning
confidence: 99%
“…Microwaving pretreatment significantly improved the DH and free radical scavenging activity of fish frame protein hydrolysates (Ketnawa & Liceaga, ). In addition, different thermal pretreatments (heating and autoclaving) significantly enhanced antioxidant activity of peptides from chicken breast muscles upon GID (Sangsawad et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The KR line—a crossbreed between a male of a Thai indigenous chicken line (Leung Hang Khao) and a female of a broiler line (Suranaree University of Technology)—was established to support smallholder farmers, to ensure food security in communities, and to contribute to preserving indigenous chicken breeds. KR meat has a unique taste—compared to broiler meat it is firmer and chewier, with lower fat and higher collagen content, giving it a higher selling price [ 10 , 11 ]. KR chickens have an average daily weight gain of 19.8–21.0 g/d, and FCR of 2.2–2.3 [ 12 ]; they are sent to the market at ca.…”
Section: Introductionmentioning
confidence: 99%
“…Poultry meat is widely consumed in many countries due to the high nutritional value, the rapid growth rate of the domestic poultry and the relatively lower costs of production than beef and pork, etc. (Kakhki, Bakhshalinejad, Hassanabadi, & Ferket, ; Sangsawad, Kiatsongchai, Chitsomboon, & Yongsawatdigul, ). Goose meat consumption has been increased in Asia and Europe, especially in Taiwan, China, and Turkey (Orkusz, Haraf, Okruszek, & Werenska‐Sudnik, ).…”
Section: Introductionmentioning
confidence: 99%
“…Poultry meat is widely consumed in many countries due to the high nutritional value, the rapid growth rate of the domestic poultry and the relatively lower costs of production than beef and pork, etc. (Kakhki, Bakhshalinejad, Hassanabadi, & Ferket, 2017;Sangsawad, Kiatsongchai, Chitsomboon, & Yongsawatdigul, 2016).…”
Section: Introductionmentioning
confidence: 99%